USE OF MOBILE TECHNOLOGIES IN COMPUTER SCIENCE LESSONS IN THE CONDITIONS OF BLENDED LEARNING (Innovative professional education, 2023)
The article highlights the experience of using mobile technologies in computer science lessons in the conditions of blended learning. It was found that the development of digital society contributes to the improvement of both mobile technology and students' ability to use it. Therefore, the use of mobile devices in lessons is possible, and sometimes necessary, especially in the conditions of the imperfect state of computer equipment in educational institutions. Blended learning allows you to combine different forms and methods of work of the teacher and students and minimize existing problems of a technical and technological nature.
Keywords: blended learning; mobile learning; cloud services in education